Biobehavioral Interactions between Endocannabinoid and Hypothalamicpituitary- adrenal Systems in Psychosis: A Systematic Review - Colizzi, Marco; Bortoletto, Riccardo; Antolini, Giulia; Bhattacharyya, Sagnik; Balestrieri, Matteo; Solmi, Marco (Current Neuropharmacology, 2024)
Background: The diathesis-stress paradigm and the cannabinoid-hypothesis have been proposed as possible pathophysiological models of schizophrenia. However, they have historically been studied independently of each other. Objective: This PRISMA 2020-compliant systematic review aimed at reappraising the interplay between the hypothalamic-pituitary-adrenal (HPA) axis and the endocannabinoid (eCB) system in psychosis- spectrum disorder risk and outcome. Methods: All pathophysiological and outcome clinical studies, concomitantly evaluating the two systems in psychosis-spectrum disorder risk and different stages of illness, were gathered from electronic databases (Pubmed, Web of Science, and Scopus), and discussed. Results: 41 eligible outputs were extracted, focusing on at least a biological measure (9 HPA-related studies: 4 eCB-interventional, 1 HPA-interventional, 1 both HPA-interventional and non-interventional, 3 non-interventional; 2 eCB-related studies: non-interventional), environmental measures only (29 studies: 1 eCB- interventional, 28 non-interventional), and genetic measures (1 study: non-interventional). Independent contributions of aberrancies in the two systems to the physiopathology and outcome of psychosis were confirmed. Also, concomitant alterations in the two systems, either genetically defined (e.g., CNR1 genetic variation), biologically determined (e.g., dysfunctional HPA axis or endocannabinoid signaling), or behaviorally imputed (e.g., cannabis use, stress exposure, and response), were consistently reported in psychosis. Further, a complex biobehavioral perturbation was revealed not only within each system (e.g., cannabis use affecting the eCB tone, stress exposure affecting the HPA axis), but also across the two systems (e.g., THC affecting the HPA axis, childhood trauma affecting the endocannabinoid signaling). Conclusion: There is a need to concomitantly study the two systems’ mechanistic contribution to psychosis in order to establish more refined biological relevance.
Keywords: Multisystem disorder